An overview of progressive advancement in ultra-high performance concrete with steel fibers - Alkadhim, Hassan Ali; Amin, Muhammad Nasir; Ahmad, Waqas; Khan, Kaffayatullah; Umbreen-us-Sahar,; Al-Hashem, Mohammed Najeeb; Mohamed, Abdullah (Frontiers in Materials, 2022)
A progressive advance in the construction sector is attained by employing ultra-high-performance concrete (UHPC) technology. Rigorous efforts have been made in this research domain to have remarkable quality levels with 150 MPa or more strength and significant durability, which was impossible before. Steel fibers incorporation in UHPC is vital in improving its mechanical characteristics. This review on the incorporation of steel fibers in UHPC evaluates, identifies and synthesizes research outcomes for creating a summary of current evidence which can contribute to evidence-based practice. This study summarized a review of the literature on steel fibers' effect on UHPC, intending to explore its essential aspects. The aim is to summarize the literature in this research domain and provide guidance for future research. Moreover, the basic requirements and materials, mixing and casting, mechanical properties, modern applications, advantages and disadvantages, and future perspectives associated with steel fibers reinforced UHPC in the construction sector are discussed. It is revealed from the conducted analysis that the most widely applied keyword is "steel fibers". Due to the graphical illustration of contributing studies, the current work may benefit academic scholars in sharing novel techniques and ideas and establishing collaborative efforts. Furthermore, the present work reveals that steel fibers have the potential to enhance the mechanical properties of UHPC; however, the large-scale production and applications of steel fiber-reinforced UHPC is controlled by parameters like fiber content, geometry etc.